Polymerase chain reaction in meat species identification - Zurak, Dora (Array, 2021)
Food is considered authentic or genuine if the product or its contents conform to the original condition and label claims. Deviations from assertions and information on the declaration are considered non-compliances with food regulations. Due to the increased awareness of the problem and negative impact of food fraud, meat consumption is significantly influenced by consumer perceptions of food quality and safety. Therefore, accurate labelling is one of the most important factors influencing consumer preferences in the selection and purchase of meat and meat products. For this reason, analytical methods to verify the authenticity of meat and meat products are important to ensure product quality, food safety and consumer protection. The substitution of meat variety is not the only criterion for determining the authenticity of meat and meat products, but also the origin of the meat, the treatment of the meat and the addition of non-meat ingredients. Polymerase chain reaction (PCR) and its derived technologies have been shown to be the most suitable methods for species identification in raw and technologically processed meat. PCR methods are mainly based on the identification of the target region of mitochondrial DNA, which allows the detection of species in a wide range of meat products, including all domestic animals as well as game meat intended for human consumption. However, they also have some drawbacks. For example, random amplified polymorphic DNA (PCR-RAPD) is not suitable for species identification in meat mixtures as well as in thermally processed meat. On the other hand, some methods are expensive, time consuming and there are difficulties in interpreting the results. In this article, the main PCR-based methods for meat species identification are presented and described.